2011
DOI: 10.1007/s13197-011-0249-8
|View full text |Cite
|
Sign up to set email alerts
|

Sorption isotherm characteristics of aonla flakes

Abstract: The equilibrium moisture content was determined for un-osmosed and osmosed (salt osmosed and sugar osmosed) aonla flakes using the static method at temperatures of 25, 40,50, 60 and 70°C over a range of relative humidities from 20 to 90%. The sorption capacity of aonla decreased with an increase in temperature at constant water activity. The sorption isotherms exhibited hysteresis, in which the equilibrium moisture content was higher at a particular equilibrium relative humidity for desorption curve than for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Al-Muhtaseb et al (2004) noticed that the hysteresis effect between desorption and adsorption isotherms depends on compositional and structural changes caused by processing methods. The observation was in agreement with an additional study by Alam and Singh (2011). They reported that the hysteresis effect was observed prominently for un-osmosed and salt-osmosed samples in comparison to sugar-osmosed samples.…”
Section: Introductionsupporting
confidence: 92%
“…Al-Muhtaseb et al (2004) noticed that the hysteresis effect between desorption and adsorption isotherms depends on compositional and structural changes caused by processing methods. The observation was in agreement with an additional study by Alam and Singh (2011). They reported that the hysteresis effect was observed prominently for un-osmosed and salt-osmosed samples in comparison to sugar-osmosed samples.…”
Section: Introductionsupporting
confidence: 92%
“…Moreover, Jain et al (2010) considered the Oswin as a superior model in describing the sorption characteristics of osmotically dehydrated papaya cubes. A number of studies have shown that GAB model has been successful in providing reasonable fit to sorption isotherms of several foods (Reddy and Chakraverty 2004;Erbas et al 2005;Togrul and Arslan 2006;Alam and Singh 2011;Rakshit et al 2011;Koua et al 2012). The results have shown that Smith model was in good agreement with the experimental sorption data of paddy throughout the whole water activity range.…”
Section: Modeling Sorption Isothermmentioning
confidence: 83%
“…Quantitative analysis was performed using the external standard method (ferrous sulfate, 0.1-2 mmol), correlating the absorbance (λ 450 nm) with the concentration, and the spectrophotometric readings were carried out on a Varian Cary 50 Scan spectrophotometer (Varian, Leini, Turin, Italy). The results are expressed as millimoles of Fe 2+ per g of dry extract [20].…”
Section: Discrimination Of the Different E Spinosus Organs Using Mult...mentioning
confidence: 99%
“…Quantitative analysis was done using the external standard method, employing ferrous sulfate in the range of 0.1-2 mmol, correlating the absorbance at λ = 593 nm with the concentration. The results were expressed as millimoles of Fe 2+ per g of dry extract [20].…”
Section: Ferric Reducing Antioxidant Assay (Frap Assay)mentioning
confidence: 99%